On the temperature dependence of oxygen ionic conductivity of 10Sc1CeSZ electrolytes - Kyrpa, O.L. (Электронная микроскопия и прочность материалов, 2013)
The dependency of ionic oxygen conductivity of 10Sc1CeSZ electrolyte made of different nanosized zirconia powders those differ by their impurities and manufacturing technologies, and sintered in air at different temperatures after uniaxial pressing are analyzed in terms of their Arrhenius equations in 250—850 °C temperature range. Deviation from a typical linear dependence of conductivity on temperature that is the most clearly visible in the electrolyte made of the purest powder is observed. The inflection point is determined by powder properties and is practically independent on sintering temperature.